The impact of long-term care needs on the socio-economic deprivation of older people and their families: A scoping review protocol. - Rossella Martarelli; Georgia Casanova; Giovanni Lamura (PLoS ONE)
Major global problems such as population ageing, long-term care and the socio-economic burden of chronically ill older people and their families are urgent issues. Research in this field contributes to the growing international literature on health-related quality-of-life instruments, but little is known about the links between the related variables. Thus, the scoping review this protocol refers to plans to examine the socio-economic consequences of older people's poor health on their economic conditions and their families. In particular, the main aims are: a) to map the main concepts that characterize the body of the reference literature; b) to identify conceptual gaps or unexplored research areas to be addressed; c) to illuminate the difficulties that affect a large number of families with older members to care for, with particular attention to the concept of socio-economic deprivation, which includes material living conditions as well as social aspects (e.g. in the form of loneliness experienced as a consequence of health disorders). This protocol paper fulfils the purpose of clarifying the planned methodological phases, including the sub-phases, and listing the techniques used. A three-step approach is being applied, consisting of: pre-planning phase, protocol phase, and conduction and reporting phase. The preliminary stages of the protocol design are part of a dedicated project within the Open Science Framework platform and included in a Research Square preprint. This proposed project will contribute to multidisciplinary research on the connections between ill health and poverty, and could support critical reflections on the current evidence and guide future policies to alleviate this double burden.